1% Alendronate Gel as Local Drug Delivery in the Treatment of Class II Furcation Defects: A Randomized Controlled Clinical Trial. Issue 3 (1st March 2013) - Pradeep, A.R.; Kumari, Minal; Rao, Nishanth S.; Naik, Savitha B.
Abstract : Background: Alendronate (ALN), an aminobisphosphonate, is known to stimulate the formation of osteoblast precursors to promote osteoblastogenesis. The present study aims to explore the efficacy of 1% ALN gel as a local drug delivery system in adjunct to scaling and root planing (SRP) for the treatment of Class II furcation defects in comparison with placebo gel. Methods: A total of 69 mandibular Class II furcation defects were randomized and treated with either 1% ALN gel or placebo gel. Clinical parameters were recorded at baseline, 3 months, 6 months, and 12 months, and radiographic parameters were recorded at baseline, 6 months, and 12 months. Defect fill at baseline, 6 months, and 12 months was calculated on standardized radiographs using image analysis software. Results: Mean probing depth (PD) reduction and mean relative vertical (RVCAL) and horizontal (RHCAL) clinical attachment level gain were shown to be greater in the ALN group than the placebo group at 3, 6, and 12 months. Furthermore, a significantly greater mean percentage of bone fill was found in the ALN group (32.11% ± 6.18%, 32.66% ± 5.86%), compared with the placebo group (2.71% ± 0.61%, 1.83% ± 1.51%), at 6 and 12 months, respectively. Conclusions: The results of the present study show that local delivery of 1% ALN into a Class II furcation defect stimulates a significant PD reduction, RVCAL and RHCAL gains, and improved bone fill compared with placebo gel as an adjunct to SRP. ALN can provide a new direction in management of furcation defects.